CRIMINAL LIABILITY FOR COLLABORATIVE ACTIVITIES: ANALYSIS OF COURT PRACTICE - Lysko, Tetyana; Litvinchuk, Bohdana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to carry out an in-depth analysis of collaborative activity as one of the phenomena caused by the invasion of the Russian Federation on the territory of Ukraine, consideration and definition of the problem of collaborationism as a modern phenomenon that arose and, unfortunately, continues to exist in connection with the occupation of part of the territory of Ukraine by the aggressor country, clarifying the features of collaborationism as a criminal offense against the foundations of national security of Ukraine, carrying out a comparison of collaborationism with related criminal offenses. Research methods: the basis of research consists of general methods of thinking, functional, system, structural method, as well as such research methods as analysis, synthesis, systematization and generalization. The components of the methodological base are objectivity and a combination of critical and rational, constructive approaches. Results: an analysis of the composition of the criminal offense provided for in Art. 111-1 of the Criminal Code of Ukraine, court verdicts under the article on collaborative activity were investigated, scientific approaches to the concept of collaborationism were clarified, similar and distinctive features of articles 111 (Treason) and 111-1 (Collaborative activity) of the Criminal Code of Ukraine were compared and analyzed. Discussion: definition of the concept of «collaborationism»; features of collaborationism in Ukraine; the importance of establishing responsibility for collaborative activities; distinguishing collaborationism and other crimes against the foundations of Ukraine’s national security; the state of legislation regarding collaborative activities in Ukraine.